Epley’s maneuver versus brandt-daroff exercise for treatment of unilateral idiopathic BPPV of posterior semicircular canal: a comparative study - M., Muniraju; Sangoli, Bhavana (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Posterior canal benign paroxysmal positional vertigo (BPPV) is the most common peripheral cause of vertigo. The Dix-hallpike maneuver (DHM) is the gold standard test for diagnosis and elicits a characteristic nystagmus with vertigo at the same time. Several physical treatments have been described for repositioning the displaced otoconial particles. The aim of the study was to determine the differences in the resolution of BPPV on short and on long-term follow-up between epley’s and Brandt-Daroff exercise and to determine whether both exercise may modify the likelihood of recurrence over time. Methods: Out of 60 patients, 30 underwent Epley’s maneuver and the rest underwent Brandt-Daroff exercise after confirming the posterior canal BPPV on Dix-Hallpike test. Patients were followed weekly until symptom resolution and they become negative on Dix-Hallpike test. The patients were followed for six months and the rates of resolution and the recurrence compared between two groups. Results: After one week, 70% showed complete resolution of symptoms with none reporting a recurrence after Epley’s maneuver and 46.7% of the Brandt-Daroff exercise. After 6 months the resolution rates and recurrence rates were similar between both the groups with no statistically significant difference. Conclusions: Epley’s is more effective treatment and as safe as B-D exercise in the short term for BPPV and although it does not reduce the probability of recurrence in the 6 months follow-up period compared with B-D exercise.